The effects of ischemia on peripheral myelinated nerve - Weerasuriya, A. (My University, 1974)
The abnormal resistance at peripheral nerve to ischaeoia observe ! i n c e r t a i n disease conditions - diabetes n e l l i tus, chronic l i v o r disease, notor n«i»rone disease and allexan-diah ^>test has boon — p l a t a s r t by Semevirfttne and P e i r i s on the '«als of a defective periaxonal diffusion b a r r i e r * I t i a thought that i n the healthy nerves during lechao^la, the intact barrier serves to accumulate the E # leasing free the axon against the axona1 surface thus causing a depolarisation conduction block- In t h is study the e f f e c t of increasing the K* cent nt within the periaxonal space, on nerve e x c i t a b i l i t y have been investigated* The e f f e c t of iachaowia oa the peripheral nerve of these fiyporkalacaic cats ha* also b «en studied to ascertain the role of K* dynamics i n tha periaxonal space la the isehaeelc 1 m o t i v a t i o n process. In the second part of the study an attempt Has been »ade to identify this barrier s t r u c t u r a l l y and to doooostrate h i s t o l o g i c al encages of t h i s barrrler i n the d i a b e t i c condition* Has results of these exr»erinent* conple^ent the res a l t a obtained free physiological etndloe on the periaxonal d i f f u s i o n barrier of diabetic nerve• From the r e s u l t * of t h i s study It has been concluded that the para we >fsi gap substance at the nodes of Ranvler constitute the postulated periaxonal diffusion b a r r i e r * Further* a reduction In the cation hlndlne capacity of t h i s cap rebalance i n • 106 » the nerves of diabetic subjects and alloxan«>diabctle rata has been demonstrated. Tha possible antecedent biochemical changes which lead to the altered staining propertiss of the gap substance are examined. \ correlation between Schwann c e ll ostabolisn in segmental deayelin&tlon and chAJigee of the gap substance i s suggested